Development and qualification of a VH-TDMA for the study of pure aerosols. Issue 2 (1st February 2019) - Oxford, Christopher R.; Rapp, Charles M.; Wang, Yang; Kumar, Purushottam; Watson, Daniel; Portelli, Julianna L.; Sussman, Eric A.; Dhawan, Steven; Jiang, Jingkun; Williams, Brent J.
Abstract: We create and qualify a Volatility and Hygroscopicity Tandem Differential Mobility Analyzer (VH-TDMA) for the study of aerosols. This VH-TDMA measures size distributions, volatility, and hygroscopicity and includes an auxiliary conditioner that allows quick connection to other external aerosol conditioners. The differential mobility analyzers are not temperature controlled, allowing the surrounding environment to influence the measurement conditions, and this is fully accounted for when measuring aerosol volatility and hygroscopicity. For the volatility conditioner, the VH-TDMA uses a 15 m coil of tubing in an oven to evaporate aerosol samples at elevated temperatures. We measured several single component model aerosols to qualify the differential mobility particle sizer (DMPS) channel and each of the conditioners: hygroscopicity and volatility. Due to insufficient power supply calibration in this study, the TDMA channel is limited to particle sizes greater than 70 nm. The DMPS channel was able to reproduce ammonium sulfate size distributions when compared to common scanning mobility particle sizers. For hygroscopicity, the standard deviation in the measured ammonium sulfate growth factors was 0.03 over a 4-h experiment. From this data, the TDMA has an observed relative humidity error of ±0.6% with manufacturer reported error of ±1.2% relative humidity. The volatility channel reproduced the previously published saw tooth pattern of room temperature saturation vapor pressures from atomized C3-C9 diacids. The maximum percent difference in room temperature saturation vapor pressure was approximately 80%. The enthalpy of sublimation derived from the diacids increased monotonically (except for suberic acid) and resembled measurements from mass effusion techniques. Copyright © 2019 American Association for Aerosol Research